The Fate of "No-Fault" in America - Gaskins, Richard (Victoria University of Wellington Law Review, 2003)
Outside New Zealand other countries debated possible "no-fault" reforms. Why did other countries not follow the same pattern as New Zealand in the 1960s? This article looks at the different policy outcomes in the United States, where no-fault proposals of limited scale were vigorously debated in the 1960s, and where more comprehensive approaches (including ideas drawn from the New Zealand ACC) struggled to gain political traction amidst the growing trend to litigation in the 1970s. Also taking shape in the United States was a new conceptual approach to the problems of personal injury, using the language and methods of welfare economics, which utterly transformed the academic debate. The writings of Guido Calabresi may suggest how, after 1980, the core definitions and distinctive principles advanced by Woodhouse seemed lost in translation, especially after these American methods found their way into New Zealand ACC debates.